Indian Judiciary as a Catalystic Agent of Social Change - Ghosh, Arup (Journal of Humanities and Social Sciences Studies, 2020)
Social Change is concerned with the question of how our society changes, in what directions and by what forces the change occurs day by day. By social change we basically mean such alterations that occur in social organization, that is, structures and functions of society. Man is a social animal, so by social change we mean, there has been a change which taken place in human thinking, values and lifestyle also. Here in this paper we will discuss about the catalytic role of Indian Judiciary particularly the role of Indian Supreme Court in promoting social change in India. Indian judiciary through its judicial verdict and interpretations of the Constitution plays a major role in inducing social change. There are many areas where the judiciary takes active role for social change. Some of these areas relating to social justice with special focus on women and children, fundamental right to life, accountability in public governance and environmental adjudication. Through various cases Indian Judiciary plays as an agent of social change.